2018
DOI: 10.1111/ijcs.12461
|View full text |Cite
|
Sign up to set email alerts
|

Propensity to plan, financial capability, and financial satisfaction

Abstract: Propensity to plan is an indicator of financial capability that contributes to consumer financial well‐being. Previous research has shown that propensity to plan is positively related to objective financial well‐being but little research was found to examine its association with subjective financial well‐being. Using financial satisfaction to measure subjective financial well‐being, this study addressed this research gap and had three objectives: (1) to explore factors associated with propensity to plan, (2) t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
143
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 108 publications
(162 citation statements)
references
References 45 publications
13
143
1
5
Order By: Relevance
“…It is expected that more mandatory personal finance courses in high school taught by teachers who are better trained in personal finance will be beneficial to foster desirable financial behaviours amongst young adults. Financial literacy and financial management practices, including budgeting (Xiao & O'Neill, ), credit card debt management (Shen, Sam Abdoul, & Jones, ) and saving with different purposes (Nam, Lee, McMahon, & Sherraden, ), especially emergency savings (Babiarz & Robb, ), can be incorporated into middle and high school curriculums to teach future young adults to manage their finances. Since most young adults do not go to college, high schools assume more responsibilities in helping students foster useful soft skills such as critical thinking, analysis and problem‐solving abilities.…”
Section: Resultsmentioning
confidence: 99%
“…It is expected that more mandatory personal finance courses in high school taught by teachers who are better trained in personal finance will be beneficial to foster desirable financial behaviours amongst young adults. Financial literacy and financial management practices, including budgeting (Xiao & O'Neill, ), credit card debt management (Shen, Sam Abdoul, & Jones, ) and saving with different purposes (Nam, Lee, McMahon, & Sherraden, ), especially emergency savings (Babiarz & Robb, ), can be incorporated into middle and high school curriculums to teach future young adults to manage their finances. Since most young adults do not go to college, high schools assume more responsibilities in helping students foster useful soft skills such as critical thinking, analysis and problem‐solving abilities.…”
Section: Resultsmentioning
confidence: 99%
“…To test H3, planning was selected as a behaviour at the high end of the behavioural hierarchy. Planning behaviour is associated with high economic status and financial capability variables, and contributing to financial well‐being (Xiao & O'Neill, ). Figures were constructed to compare budgeting and planning behaviour by financial resource variables.…”
Section: Resultsmentioning
confidence: 99%
“…The extant literature also provides evidence of a positive connection between proactive financial behaviors and well-being beyond the financial domain. For instance, several studies using cross-sectional data from young adults, including college students, have found a positive association between proactive financial behaviors and personal well-being (Shim et al, 2009;Xiao and O'Neill, 2018), psychological well-being (Britt et al, 2015;Kim et al, 2003) and life satisfaction (Gutter and Copur, 2011;Norvilitis and MacLean, 2010). Some researchers have found similar associations over time.…”
Section: Proactive Financial Behavior and Subjective Well-beingmentioning
confidence: 97%